PEMANFAATAN MEDIA PEMBELAJARAN SOSIOLOGI BERBASIS INTERNET OLEH GURU MA ISLAMIYAH PONTIANAK - Purnawati, Emonika; Warneri, Warneri; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study learned to learn about, "using internet-based sociology learning media". The research method used is descriptive in the form of qualitative research. The source of this research data is the 2015 PPAPK sociology education student FKIP UNTAN. Data collection techniques used were interview techniques and documentation, while the data collection tools used were interview guides and documentation. The analysis in this study was presented in a descriptive qualitative manner using informants as many as 5 people. The problem in this thesis is, "The Utilization of Internet-Based Learning Sociology Media by Teachers MA Pontianak ISLAMIC". With sub-problems 1. What is the process of learning internet-based media in sociology learning by teachers in Pontianak ISLAMIAH MA?!, 2. Does the teacher use the website in making sociology learning material in the MA ISLANDYAH?!. 1. Teachers make use of internet media for the learning process in class to help teachers in finding teaching materials. If the teaching material is provided in the book or completes less or is still incomplete. 2. Teachers make use of the internet consisting of web sites in the learning process with online learning materials, by assigning students to (downlond) the learning material as additional material that supports this material not in the textbook or LKS. Keywords: Use of the internet, learning resources, website